Raman and IR-ATR spectroscopy studies of heteroepitaxial structures with a GaN:C top layer. (16th August 2017) - Cerqueira, M F; Vieira, L G; Alves, A; Correia, R; Huber, M; Andreev, A; Bonanni, A; Vasilevskiy, M I
Abstract: This work, motivated by the technologically important task of determination of carbon dopant location in the GaN crystal lattice, employed Raman spectroscopy, with both resonant and non-resonant excitation, and infrared (IR) spectroscopy, in the attenuated total reflection (ATR) configuration, to study lattice vibration modes in a set of carbon-doped GaN (GaN:C) epilayers grown by metalorganic vapour phase epitaxy. We analyse Raman and IR-ATR spectra from the point of view of possible effects of the carbon doping, namely: (i) local vibration mode of C atoms in the nitrogen sublattice (whose frequency we theoretically estimate as 768 cm −1 using an isotope defect model), and (ii) shift in the positions of longitudinal modes owing to the phonon–plasmon coupling. We find only indirect hints of the doping effect on the resonant Raman spectra. However, we show theoretically and confirm experimentally that the IR-ATR spectroscopy can be a much more sensitive tool for this purpose, at least for the considered structures. A weak perturbation of the dielectric function of GaN:C, caused by the substitutional carbon impurity, is shown to produce a measurable dip in the ATR reflectivity spectra at ≈770 cm −1 for both p - and s -polarizations. Moreover, it influences a specific (guided-wave type) mode observed at ≈737 cm −1, originating from the GaN layer, which appears in the narrow frequency window where the real parts of the two components of the dielectric tensor of the hexagonal crystal have opposite signs. This interpretation is supported by our modelling of the whole multilayer structure, using a transfer matrix formalism.